2021
DOI: 10.1007/s11356-021-14927-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential application and beneficial effects of a marine microalgal biomass produced in a high-rate algal pond (HRAP) in diets of European sea bass, Dicentrarchus labrax

Abstract: Microalgae have been used as live food in aquatic species. In recent years, the interest in microalgae has considerably increased, thanks to the evolution of production techniques that have identified them as an ecologically attractive aquafeed ingredient. The present study provides the first data about the effects of dietary inclusion of a microalgae consortium grown in a high-rate algal pond system on zootechnical performance, morphometric indices, and dietary nutrient digestibility as well as morphology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…In the current study, after a 12-week feeding period on N. oculate and Schizochytrium and Spirulina species combination enriched with omega-3, we achieved our targeted goal concerning maximum fish production and an enhanced fillet quality with omega-3 (n-3) fatty acids. In accordance, dietary feeding on Schizochytrium species for Nile tilapia [ 11 ] and Nannochloropsis species for European sea bass [ 64 ] improved their growth rates to certain limits, while feeding of Nile tilapia in our study on a combination of selected microalgae enhanced the growth performance parameters of Nile tilapia more prominently, especially with increasing their inclusion levels (up to 3%). Besides, more efficient digestion due to higher digestive enzymes’ activities was detected in groups exhibiting improved growth-related parameters and those fed higher levels of microalgae mixtures, which came in the same line with the findings stated previously [ 65 , 66 , 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 78%
“…In the current study, after a 12-week feeding period on N. oculate and Schizochytrium and Spirulina species combination enriched with omega-3, we achieved our targeted goal concerning maximum fish production and an enhanced fillet quality with omega-3 (n-3) fatty acids. In accordance, dietary feeding on Schizochytrium species for Nile tilapia [ 11 ] and Nannochloropsis species for European sea bass [ 64 ] improved their growth rates to certain limits, while feeding of Nile tilapia in our study on a combination of selected microalgae enhanced the growth performance parameters of Nile tilapia more prominently, especially with increasing their inclusion levels (up to 3%). Besides, more efficient digestion due to higher digestive enzymes’ activities was detected in groups exhibiting improved growth-related parameters and those fed higher levels of microalgae mixtures, which came in the same line with the findings stated previously [ 65 , 66 , 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, previous studies reported no effects or even a reduction of intestinal area, or villus length and width in carnivorous fish fed diets supplemented with individual Ulva sp., Gracilaria sp., Chlorella sp., or Nannochloropsis sp. ( 41 , 54 , 94 , 95 ), or their mixtures ( 54 , 79 , 80 ). Fish fed the control diet (Algae0) had the lowest number of goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…They observed an improvement in body weight, length, and survival rate by 35.75%, 21.17%, and 33%, respectively, compared to the control diet. Likewise, fishes fed with microalgal consortium manifested well-maintained digestive histomorphology because it can enhance the enzymatic activity of maltase, sucrase-isomaltase, and ɤ-glutamil transpeptidase in the distal intestine [125]. A recent study has demonstrated the benefits of using microalgae as a substitutive feed ingredient in dairy cattle diets [126].…”
Section: Marine Microalgae As Feed For Aquatic and Terrestrial Animalsmentioning
confidence: 99%
“…is often utilized as feed for rotifers to improve its EPA content, Isochrysis sp. is used to enhance DHA content -glutamil transpeptidase in the distal intestine [125]. A recent study has demonstrated the benefits of using microalgae as a substitutive feed ingredient in dairy cattle diets [126].…”
Section: Marine Microalgae As Feed For Aquatic and Terrestrial Animalsmentioning
confidence: 99%